Mediating effects of religious/spiritual coping on mental health - Matos , Maria de Lourdes Ferreira Medeiros de; Almeida , Simonton Barcelos França de; Fuzikawa, Cintia Satiko; Santos, Francisco de Assis Souza dos (Seven Editora, 2023)
The beneficial assets of religious/spiritual coping in mental health have been considered beneficial as coping strategies for physical and mental illnesses for many individuals, playing a significant role in their lives and can help them cope with their problems. In this sense, the aim of this study is to highlight the mediating effects of religious/spiritual coping on mental health. The study was developed through a bibliographic research, with a qualitative approach, with a search in the Scielo and PubMED databases, available in Portuguese and English, without date delimitation. The descriptors used in the search were coping, mental health, spirituality, religiosity. In this review, it was found that R/E is positively related to coping, resilience, well-being, happiness, hope, self-control and self-esteem, suggesting that the higher the R/E, the better mental health. It was concluded that the effects of religious/spiritual coping on mental health are determined, at least partially, by the structures of orientation and meaning that are strongly embedded in individual internal schemes, serving to cushion the consequences and impact of negative events and increase subjective well-being. DOI:https://doi.org/10.56238/globalhealthprespesc-054